Biomimetic Design for Adaptive Building Façades: A Paradigm Shift towards Environmentally Conscious Architecture - Ali M. A. Faragalla; Somayeh Asadi (Energies, 2022)
A change in thinking has been ongoing in the architecture and building industry in response to growing concern over the role of the building industry in the excessive consumption of energy and its devastating effects on the natural environment. This shift changed the thinking of architects, engineers, and designers in the initial phases of a building’s design, with a change from the importance of geometry and form to assessing a building’s performance, from structure to a building’s skin, and from abstract aesthetics to bio-climatic aesthetics. In this context, sustainable, intelligent, and adaptive building façades were extensively researched and developed. Consequently, several typologies, strategies, and conceptual design frameworks for adaptive façades were developed with the aim of performing certain functions. This study focuses on the biomimetic methodologies developed to design adaptive façades because of their efficiency compared to other typologies. A comprehensive literature review is performed to review the design approaches toward those façades at the early stage of design. Then, the theoretical bases for three biomimetic frameworks are presented to gain an overall understanding of the concepts, opportunities, and limitations.